2019
DOI: 10.1038/s41598-019-47719-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subcutaneous and omental adipose tissue in patients with obesity and with different degrees of glucose impairment

Abstract: Although obesity represents a risk factor for the development of type 2 diabetes mellitus (T2DM), the link between these pathological conditions is not so clear. The manner in which the different elements of adipose tissue (AT) interplay in order to grow has been suggested to have a role in the genesis of metabolic complications, but this has not yet been fully addressed in humans. Through IHC, transmission electron microscopy, cytometry, and in vitro cultures, we described the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…This vicious cycle continues with tumor necrosis factor-alpha and IL-1β secreted by M1 macrophages, further impairing adipogenic differentiation, with reduced adipogenic gene expression in subcutaneous AT and, in some cases, increased numbers of small adipocytes ( 48 , 57 , 58 ). In contrast, normoglycemic obese individuals show an increase in the percent of adipose progenitors within their tissue compared with both pre-diabetic and T2D obese subjects ( 59 ). MHO individuals benefit from a positive insulin sensitizing cycle, where anti-inflammatory signals from adipocytes result in M2 macrophage polarization, which promotes healthy adipocyte hyperplasia and further anti-inflammatory signaling from adipocytes.…”
Section: Adipocyte Function and Adipogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…This vicious cycle continues with tumor necrosis factor-alpha and IL-1β secreted by M1 macrophages, further impairing adipogenic differentiation, with reduced adipogenic gene expression in subcutaneous AT and, in some cases, increased numbers of small adipocytes ( 48 , 57 , 58 ). In contrast, normoglycemic obese individuals show an increase in the percent of adipose progenitors within their tissue compared with both pre-diabetic and T2D obese subjects ( 59 ). MHO individuals benefit from a positive insulin sensitizing cycle, where anti-inflammatory signals from adipocytes result in M2 macrophage polarization, which promotes healthy adipocyte hyperplasia and further anti-inflammatory signaling from adipocytes.…”
Section: Adipocyte Function and Adipogenesismentioning
confidence: 99%
“…Increased interstitial fibrosis due to excess collagen deposition likely decreases ECM flexibility and reduces tissue plasticity, which leads to adipocyte dysfunction and immune cell infiltration ( 66 ). Insulin-resistant individuals demonstrate aberrant ECM deposition and insufficient ECM breakdown ( 59 , 67 ).…”
Section: Extracellular Matrix Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence (IF) analyses have shown decreased capillary density in the sWAT (number of capillaries/tissue area and number of capillaries/adipocyte) [ 4 ] and vWAT (number of capillaries/tissue area) [ 5 ] of patients with obesity compared to lean subjects. Similarly, immunohistochemical (IHC) analyses showed lower capillary density (number of capillaries/tissue area) in the sWAT and vWAT of normoglycemic, prediabetic and type 2 diabetes mellitus (T2DM) patients with obesity compared to lean subjects [ 6 ]. Moreover, IHC analyses showed lower capillary density (number of capillaries/tissue area and number of capillaries/adipocyte) in the sWAT of patients with obesity compared to overweight patients and ex vivo experiments revealed reduced number of capillary branches in sWAT explants from patients with obesity compared to explants from overweight patients [ 7 ].…”
Section: Obesity-induced Capillary Rarefaction In Different Tissuementioning
confidence: 99%
“…Consistent with this, when adipocyte size is sorted based on size distribution instead of average size, elevated frequency of very small SAT adipocytes and reduced numbers of larger adipocytes were reported in overweight subjects with IR and T2D [ 41 , 44 , 45 ]. However, other studies have also shown increased mean adipocyte size, particularly in VAT, in obese subjects with abnormal metabolic phenotype [ 46 , 47 , 48 ].…”
Section: Healthy and Unhealthy Responses Of Adipose Tissue To Excementioning
confidence: 99%